PENERAPAN MODEL DRILLS DALAM PEMBELAJARAN MATEMATIKA BERBASIS KOMPUTER PADA SISWA KELAS XI IPA MAN 1 LUBUKLINGGAU - Riduan Febriandi (LP4MK STKIP PGRI Lubuklinggau, 2020)
This study aims to determine the learning outcomes of students in class XI IPA MAN 1 in the Lubuklinggau Model 2017/2018 academic year after applying the model of drills in computer-based mathematics learning. This type of research used in the form of quasi-experimental conducted without a comparison class with Pre-test and Post-test design. The population is all students of class XI Science consisting of 111 students and as a sample are students of class XI Science 2 consisting of 37 students. Data collection was performed using a test technique, the test data collected were analyzed using t-test at a significant level α = 0.05. Mathematics learning outcomes of students of class XI IPA 2 MAN 1 Lubuklinggau Model for the 2017/2018 academic year after participating in Mathematics learning using computer-based drills models were significantly completed with an average test score of 83.98 with the percentage of students completing 72.97% . Students are increasingly interested in each meeting and students are more active and give good results. Based on the analysis of the data it can be concluded that the computer-based model of drills is effective for use in the study of metaphorics.